2007
DOI: 10.1038/sj.mp.4002114
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between screened NIMH and clinically interviewed control samples on neuroticism and extraversion

Abstract: The National Institute of Mental Health (NIMH) has supported the collection of DNA samples on over 4000 subjects for use primarily as controls in psychiatric genetic studies. These subjects, though screened online, were not directly interviewed or assessed on family history. We compared this sample to one that was directly interviewed using structured diagnostic assessments on comparable measures of neuroticism and extraversion. The screened sample completed an online self-report based on the Composite Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Additional control samples used for N4001 genotyping (n = 679) were also matched for ancestry and had been screened for the absence of OCD and related disorders [25].…”
Section: Resultsmentioning
confidence: 99%
“…Additional control samples used for N4001 genotyping (n = 679) were also matched for ancestry and had been screened for the absence of OCD and related disorders [25].…”
Section: Resultsmentioning
confidence: 99%
“…Absence of SS may protect against psychobiological responses to stressful events, and is consistent with the lower rates of depressive and anxiety disorders in the low-risk group (Weissman et al, 2006; Weissman et al, 2005). Although we cannot elucidate why the low-risk group deviates from population-expected frequencies, it should be noted that probands in the low-risk group were selected to have no history of any psychopathology and thus may not be reflective of population-based controls (Talati et al, 2008). The low-risk group also had higher rates of the heterozygous (SL) genotypes [67% observed, vs. 47% expected], which has been shown to be advantageous via increasing fitness and flexibility to adapt (Cools and Robbins, 2004; Gosso et al, 2008)].…”
Section: Discussionmentioning
confidence: 99%
“…The CIDI-SF, administered by trained lay interviewers, provides screening assessments of community samples for common mental disorders. Studies have found moderate agreement between CIDI-SF diagnoses and those obtained by face-to-face diagnostic clinical interviews (34,35). Probable diagnoses were obtained for past-year major depression, generalized anxiety disorder, and panic attacks using DSM-III-R criteria (36).…”
Section: Methodsmentioning
confidence: 99%